Surgery First Approach to Correct Gummy Smile in an Adult Female - Sujeeth Kumar Shetty; Nitin V Muralidhar; T Jerusha (Advances in Human Biology)
Vertical maxillary excess associated with long face syndrome or a hyperdivergent growth pattern gives patients an excessive gummy smile with overexposure of the upper anterior teeth. This results in a very unesthetic gummy smile and facial profile for the patient. Hyperdivergent growth patterns also affect the normal maxilla-mandibular relationship, as there is a presence of mandibular clockwise rotation, which compromises the functional component. Hence, this condition leads to poor aesthetics and function. This condition is treated by a non-surgical approach using Temporary anchorage device (TAD) s in recent years. However, for an excessive gummy smile, the ideal treatment option is orthognathic surgery combined with orthodontic treatment to correct the dental irregularities. In this case report, we will discuss gummy smile correction in a young adult female using a surgery-first approach, with a combined orthodontic and orthognathic surgical treatment, highlighting absolutely no forward movement of the mandible after the maxillary impaction, thus maintaining perfect Class I molar and canine relations.